Cow excrements enhance the occurrence of tetracycline resistance genes in soil regardless of their oxytetracycline content - Kyselková, Martina; Jirout, Jiří; Chroňáková, Alica; Vrchotová, Naděžda; Bradley, Robert; Schmitt, Heike; Elhottová, Dana (Chemosphere, 2013)
Fertilizing soils with animal excrements from farms with common antibiotic use represents a risk of disseminating antibiotic resistance genes into the environment. In the case of tetracycline antibiotics, it is not clear, however, whether the presence of antibiotic residues further enhances the gene occurrence in manured soils. We established a microcosm experiment in which 3 farm soils that had no recent history of fertilization with animal excrements were amended on a weekly basis (9 times) with excrements from either an oxytetracycline-treated or an untreated cow. Throughout the study, the concentration of oxytetracycline in excrements from the treated cow was above 500 μg g(-1)dw, whereas no oxytetracycline was detected in excrements from the healthy cow. Both excrements contained tetracycline resistance (TC-r) genes tet(L), tet(M), tet(V), tet(Z), tet(Q) and tet(W). The excrements from the treated cow also contained the tet(B) gene, and a higher abundance of tet(Z), tet(Q) and tet(W). Three weeks after the last excrement addition, the individual TC-r genes differed in their persistence in soil: tet(Q) and tet(B) were not detectable while tet(L), tet(M), tet(Z) and tet(W) were found in all 3 soils. There were, however, no significant differences in the total number, nor in the abundance, of TC-r genes between soil samples amended with each excrement type. The oxytetracycline-rich and the oxytetracycline-free excrement therefore contributed equally to the increase of tetracycline resistome in soil. Our results indicate that other mechanisms than OTC-selection pressure may be involved in the maintenance of TC-r genes in manured soils.
Keywords: Cattle; Animals; skot; Oxytetracycline; Soil Pollutants; zemědělství; Manured soil; bakteriální geny; Tetracycline resistance; látky znečišťující půdu; Environmental risk assessment; Cattle excrement; Anti-Bacterial Agents; Tetracycline Resistance; půdní mikrobiologie; hnůj; Manure; rezistence na tetracyklin; Tetracycline resistance gene; Soil Microbiology; Genes, Bacterial; zvířata; Soil; půda; antibakteriální látky; oxytetracyklin; Agriculture